How are regulatory oversight organisations using long-term care performance indicators: a qualitative descriptive study in 10 high-income countries - Niek Klazinga; Dionne Kringos; Mircha Poldrugovac; Anne Margriet Pot (BMJ Open, 2023)
Objectives Regulatory oversight organisations play an important role in quality stewardship in long-term care (LTC) facilities. Performance indicators are a key tool for any quality-related work. Our aim was to better understand how and what performance indicators are used by regulatory oversight organisations for long-term care facilities oversight and which features are affecting their fitness for use.Design Qualitative descriptive.Setting and participants We explored the use of LTC facility performance indicators by 10 regulatory oversight organisations from England, Ireland, Malta, New Zealand, Norway, Scotland, Singapore, Slovenia, Sweden and the Netherlands. We collected information by means of a questionnaire, 13 follow-up interviews with 20 experts from these organisations and document review.Results Performance indicators are used by participating oversight organisations to choose priority topics for audits, prioritise facilities to be audited and to identify areas within an audited facility, that require more attention. The indicators of most interest to oversight organisations are related to the dimensions of care articulated in the preset requirements on which audits are based. When the purpose of using indicators is to design a risk assessment model, the fitness for use of indicators ultimately depends on their ability to predict non-compliances on subsequent audits. When indicators are used directly by auditors, the ease of access, clear guidance to evaluate the data and the provision of contextual information are used by oversight organisations to increase fitness for use.Conclusions Oversight organisations do not use LTC facility performance indicators to assess quality, but rather to assess the risk of lower quality or of non-compliance with requirements. This risk-related purpose has to be considered when the indicators used in oversight are chosen and when other aspects of fitness for use, such as data analysis and displaying findings, are developed.